The influence of thermal radiation on unsteady free convection in inclined enclosures filled by a nanofluid with sinusoidal boundary conditions. Issue 8 (20th September 2018) - Sheremet, Mikhail A.; Pop, Ioan; Rosca, Alin V.
Abstract : Purpose: The purpose of this study is a numerical analysis of transient natural convection in an inclined square cavity filled with an alumina-water nanofluid under the effects of sinusoidal wall temperature and thermal radiation by using a single-phase nanofluid model with empirical correlations for effective viscosity and thermal conductivity. Design/methodology/approach: The domain of interest includes the nanofluid-filled cavity with a sinusoidal temperature distribution along the left vertical wall. Horizontal walls are supposed to be adiabatic, while right vertical wall is kept at constant low temperature. Temperature of left wall varies sinusoidally along y-coordinate. It is assumed in the analysis that the thermophysical properties of the fluid are independent of temperature and the flow is laminar. The governing equations have been discretized using the finite difference method with the uniform grid. Simulations have been carried out for different values of the Rayleigh number, cavity inclination angle, nanoparticles volume fraction and radiation parameter. Findings: It has been found that a growth of radiation parameter leads to the heat transfer enhancement and convective flow intensification. At the same time, an inclusion of nanoparticles illustrates a reduction in the average Nusselt number and fluid flow rate. Originality/value: The originality of this work is to analyze unsteady natural convection in a square cavity filled with a water-based nanofluid in the presence of a sinusoidal temperature distribution along one wall. The results would benefit scientists and engineers to become familiar with the analysis of convective heat and mass transfer in nanofluids and the way to predict the properties of nanofluid convective flow in advanced technical systems, in industrial sectors including transportation, power generation, chemical sectors, electronics, etc.